2017
DOI: 10.3389/fpsyg.2017.00611
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity and Academic Performance: The Role of Working Memory

Abstract: The present study examined the role of working memory in the association between childhood obesity and academic performance, and further determined whether memory deficits in obese children are domain-specific to certain tasks or domain-general. A total of 227 primary school students aged 10–13 years were analyzed for weight and height, of which 159 children (44 “obese,” 23 “overweight,” and 92 “normal weight”) filled out questionnaires on school performance and socioeconomic status. And then, all subjects fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 36 publications
4
56
1
5
Order By: Relevance
“…Our findings are also consistent with a cross-sectional study of Chinese adolescents aged 11 to 13 years that found math, Chinese, and English test scores to be higher in children with normal weight compared with children with ov/ob (22). Negative impacts of obesity on adolescents' academic performance may be explained by various mechanisms, such as poor physical and mental health with subsequent absenteeism from school, impaired cognition, and impaired working memory (22)(23)(24). Negative impacts of obesity on standardized subject test scores appeared to be more pronounced in girls.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are also consistent with a cross-sectional study of Chinese adolescents aged 11 to 13 years that found math, Chinese, and English test scores to be higher in children with normal weight compared with children with ov/ob (22). Negative impacts of obesity on adolescents' academic performance may be explained by various mechanisms, such as poor physical and mental health with subsequent absenteeism from school, impaired cognition, and impaired working memory (22)(23)(24). Negative impacts of obesity on standardized subject test scores appeared to be more pronounced in girls.…”
Section: Discussionsupporting
confidence: 92%
“…Obese children can be stigmatised by peers, family and other adults in their life, and often have a lower quality of life than peers of a healthy weight (4) . Obesity can result in the early onset of puberty in girls (5) , and overweight and obesity are associated with poor levels of academic achievement (6) . Thus, Abbreviations: BMI: body mass index; CCC: concordance correlation coefficient; LOA: limits of agreement; TEM: technical error of measurement; rTEM: relative technical error of measurement JNS JOURNAL OF NUTRITIONAL SCIENCE successful interventions in childhood and adolescence are needed to reduce the risks associated with overweight and obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Further, obesity is known to impair physical fitness and academic performance [ 13 , 14 , 15 ]. Several factors have been postulated to explain how obesity promotes decreased physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, it has been suggested that obesity-related fitness impairments are caused by neuromuscular dysfunction resulting from metabolic imbalance [ 21 ]. The association between obesity and academic performance is purported to be influenced by factors such as poor peer-relationships, low-self-esteem, and reduced cognitive abilities [ 13 ]. Though obesity is known to negatively impact physical performance, the nature of the relationship between body mass index (BMI) and aspects of physical fitness is less clear, particularly among female adolescents from low socioeconomic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation